2013
DOI: 10.1111/eos.12093
|View full text |Cite
|
Sign up to set email alerts
|

Role ofNMDAreceptors in the trigeminal pathway, and the modulatory effect of magnesium in a model of rat temporomandibular joint arthritis

Abstract: Temporomandibular joint (TMJ) arthritis is a common cause of orofacial pain. In the present study, the modulatory effects of N-methyl-d-aspartate receptors (NMDA-Rs) and magnesium were investigated in TMJ arthritis hypernociception. Male Wistar rats received an intra-articular injection of carrageenan (Cg) in the TMJ, and mechanical hypernociception was measured. The NMDA-R antagonist, MK-801, and magnesium chloride (MgCl₂ ) were administered before arthritis induction. Magnesium deficiency was promoted by fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Using the same model of pain several authors have demonstrated that MK-801 in a dose-dependent manner blocks the development of thermal hyperalgesia after systemic (Ren et al 1992a;Chen et al 2010) or local (Jackson et al 1995) administrations, as well as mechanical hyperalgesia in arthritis pain (Cavalcante et al 2013). In our study, we achieved an analgesic effect with smaller doses of MK-801 (0.5-20 μg/kg, s.c.).…”
Section: Discussionsupporting
confidence: 66%
“…Using the same model of pain several authors have demonstrated that MK-801 in a dose-dependent manner blocks the development of thermal hyperalgesia after systemic (Ren et al 1992a;Chen et al 2010) or local (Jackson et al 1995) administrations, as well as mechanical hyperalgesia in arthritis pain (Cavalcante et al 2013). In our study, we achieved an analgesic effect with smaller doses of MK-801 (0.5-20 μg/kg, s.c.).…”
Section: Discussionsupporting
confidence: 66%
“…This could be because of boron's ability to increase magnesium concentrations in the blood . Magnesium can then provide its physiological channel blocking effects on N‐methyl‐ d ‐aspartate (NMDA) receptors and reduce ion currents . The NMDA receptors affect trigeminal neurons at the trigeminal subnucleus caudalis (the orofacial nocioceptive processing center) in rats .…”
Section: Discussionmentioning
confidence: 99%
“…22 Magnesium can then provide its physiological channel blocking effects on N-methyl-D-aspartate (NMDA) receptors and reduce ion currents. [29][30][31][32] The NMDA receptors affect trigeminal neurons at the trigeminal subnucleus caudalis (the orofacial nocioceptive processing center) in rats. 33 Boron can also affect neurotransmitters because of its ability to form complexes with sugars.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies that used the carrageenan injection model to study pain in the orofacial region; it has been injected into the temporomandibular joint as an arthritis model to study orofacial pain and acute pain . In the masseter muscle, carrageenan injection was used to study inflammatory response, and as an inflammatory pain memory model …”
Section: Discussionmentioning
confidence: 99%
“…Carrageenan has been administered subcutaneously to study cutaneous inflammation/pain that can be assessed in tissues innervated by lumbar dorsal root ganglion neurons (i.e., the paw) or by trigeminal ganglion neurons (i.e., the vibrissal pad) . Carrageenan has also been injected into joints as an arthritis pain model …”
mentioning
confidence: 99%